Psoriasis Induced by Tumor Necrosis Factor-Alpha Antagonist Therapy: Case Series and Literature Overview - Tunay Sarpel,; Sibel Başaran,; Filiz Doğan Akçam,; Suhan Günaştı,; Yaşargül Denli, (Archives of Rheumatology, 2010)
Although tumor necrosis factor-alpha (TNF-α) antagonists are shown to be effective in the treatment of psoriasis, induction of psoriatic skin lesions have been seen in patients with different rheumatic conditions who were treated with TNF-α antagonists. In this case series, we report four cases that developed psoriatic lesions; in one of the cases, psoriasis was associated with two different TNF-α antagonists. Case 1: A 31-year-old man with ankylosing spondylitis developed erythematous and squamous lesions on his extremities in the 2nd week of infliximab treatment. Two months later he began to receive etanercept, and psoriatic skin lesions developed on the entire trunk and extremities, and predominantly on the scalp after one month. Case 2: A 53-year-old female with rheumatoid arthritis developed psoriatic skin lesions in the ankle region after two months' treatment with etanercept. Case 3: A 34-year-old female with ankylosing spondylitis developed psoriatic lesions on her palms after 10 months' treatment with infliximab. Case 4: A 40-year-old female with ankylosing spondylitis developed pustular lesions on her palms and soles after two years' treatment with infliximab. The patients had no personal or family history of psoriasis. The diagnosis of psoriasis was confirmed by skin biopsy in three of the cases. Psoriatic skin lesions can be induced as a result of treatment with TNF-α antagonists in patients with rheumatoid arthritis, ankylosing spondylitis and other spondyloarthropathies. The most common form is plaque or pustular pattern with palmoplantar distribution. (Turk J Rheumatol 2010; 25: 91-4)